2006
DOI: 10.1002/hed.20470
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of postoperative chemoradiotherapy for patients with unknown primary squamous cell carcinoma of the head and neck

Abstract: Postoperative chemoradiotherapy is of potential benefit to patients with unknown primary SCCHN by improving survival and reducing failures. This treatment warrants further prospective evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 47 publications
(46 reference statements)
0
25
1
3
Order By: Relevance
“…However there are no randomised studies for patients with cervical CUPs and the rationale of treatment is based on the results of primary known cancer of the head and neck and small series of patients with SCC of unknown primary [34,41,42]. In the recent report by Shehadeh et al [42], 37 patients were managed with neck dissection followed by concurrent high-dose cisplatin and irradiation of bilateral neck/mucosal sites. At a median follow-up of 42 months, 89% of the patients were alive.…”
Section: Answers To the Questions Proposedmentioning
confidence: 97%
“…However there are no randomised studies for patients with cervical CUPs and the rationale of treatment is based on the results of primary known cancer of the head and neck and small series of patients with SCC of unknown primary [34,41,42]. In the recent report by Shehadeh et al [42], 37 patients were managed with neck dissection followed by concurrent high-dose cisplatin and irradiation of bilateral neck/mucosal sites. At a median follow-up of 42 months, 89% of the patients were alive.…”
Section: Answers To the Questions Proposedmentioning
confidence: 97%
“…The optimal method of radiotherapy for NUP had been controversial for a long time, as it is difficult to conduct randomized or prospective studies of this rare disease (18). Some case studies have revealed therapeutic outcomes of NUP treated by radiotherapy combined with surgery and/or chemotherapy, which are summarized in Table 5 (3,6,9,11,16,17,(19)(20)(21). Prognostic factors for survival are reported to be nodal stages, number of positive nodes, neck dissection, histopathological grading and ECE (3)(4)(5)7,9,19,20,22,23).…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent retrospective report by Shehadeh et al, 37 patients with SQCCUP were managed with neck dissection followed by concurrent high-dose cisplatin and bilateral neck/mucosal sites irradiation [52]. A total dose of 64 Gy was administered in the involved side of the neck and 50 Gy to uninvolved neck and mucosal sites.…”
Section: Combined Modality Approachesmentioning
confidence: 99%
“…To the best of our knowledge there are only 4 retrospective studies with approximately 100 patients treated with various cytotoxic drugs (platinum or non-platinum). Chemotherapy was administered before, during or after radiotherapy and results in some studies were compared with historical controls [30,[50][51][52].…”
Section: Combined Modality Approachesmentioning
confidence: 99%